Photogeneration and Visualization of a Surface-Stabilized Dinitrene - Frezza, Federico; Sánchez-Grande, Ana; Canola, Sofia; Nacci, Christophe; Klívar, Jiří; Mutombo, Pingo; Chen, Qifan; Gómez-Fernandez, José María; Sánchez-Sánchez, Carlos; Berger, Jan; Ernst, Karl-Heinz; Stará, Irena G; et al. (Angewandte Chemie (International ed. in English), 2025)
Nitrenes are known as key intermediates in various chemical reactions. Nitrene transfer reactions are particularly effective for synthesizing nitrogen-containing compounds, where metal catalysts play a crucial role in controlling nitrene reactivity and selectivity. In this study, we demonstrate the formation of a stable surface-supported dinitrene on Au(111) through UV irradiation of its diazide precursor, characterized by scanning probe techniques. The photoreaction mechanism is elucidated with wavelength-dependent experiments and time-dependent density functional theory calculations. Our findings present the first real-space visualization of a metal nitrene adsorbed on a surface, highlighting its potential in catalysis and surface functionalization.
Keywords: photochemistry; nitrene; azide; metal surface; scanning probe microscopy